THE ROLE OF TASK-BASED LANGUAGE LEARNING IN ENHANCING PROFESSIONAL COMPETENCE FOR FUTURE TOURISM SPECIALISTS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
The study explores the significance of task-based language learning (TBLL) in developing professional competence among future tourism specialists. TBLL emphasizes real-world communication through tasks that mimic workplace scenarios, fostering practical language skills and intercultural awareness essential in tourism. The research highlights how TBLL promotes active learning, adaptability, and problem-solving abilities, key competencies for tourism professionals. By engaging in tasks like role-playing, project-based assignments, and simulations, students can apply their language skills in relevant contexts, enhancing both linguistic proficiency and professional expertise. The paper underscores TBLL’s role in aligning language learning with the dynamic demands of the tourism industry.